Why Voting? A Welfare Analysis - Andreas Kleiner; Moritz Drexl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Which decision rule should we use to make a binary collective choice? While voting procedures are applied ubiquitously, they are criticized for being inefficient. Using monetary transfers, efficient choices can be made at the cost of a budget imbalance. Is it optimal to do so? And why are monetary transfers used only rarely in public decision making? We solve for the welfare maximizing social choice function taking monetary transfers explicitly into account. Under a mild regularity assumption on the distribution of types, we show that the optimal anonymous social choice function is implementable through qualified majority voting. Our result shows that using a VCG mechanism is not superior to voting in general and justifies the use of voting mechanisms. It thereby could explain why many decision rules employed in practice do not rely on monetary transfers.
Keywords: D70; D82; H41; 330